FREQUANCY OF HELICOBACTER PYLORI IN CASES WITH NONSPESIFIC GASTRITIS IN ERZURUM REGION - N. OKÇU; M. Derya ONUK; Tahir BURAN; Ersin AKARSU; M. Akif ÇİFTLİOĞLU (Turkish Journal of Gastroenterology, 2020)
-